Loser in Fight but Winner in Love: How Does Inter-Male Competition Determine the Pattern and Outcome of Courtship in Cricket Gryllus bimaculatus? - Vedenina, Varvara Yu.; Shestakov, Lev S. (Frontiers in Ecology and Evolution, 2018)
Animal females are generally assumed to prefer males that win fights. However, a growing number of studies in numerous animal taxa demonstrate no correlation between male fighting ability and their attractiveness, or even female preferences for fight losers. One of the methods to measure female preferences employs no-choice tests that evaluate a female's latency to mating when placed with a single male. Considering that courtship behavior generally contains multimodal signaling, we analyzed 19 behavioral elements demonstrated by both sexes of the cricket Gryllus bimaculatus during courtship. To estimate male dominance status, males were preliminarily tested in two rounds of fights. Females mounted males with different fighting ability equally often, but the latencies from the start of antennal contact to mount were shorter in fight losers than fight winners. During courtship, males with high fighting ability demonstrated one of the elements of agonistic display, rocking the body, more frequently, and for longer durations than males with low fighting ability. This element was negatively correlated with singing in fight winners but was positively correlated with singing a courtship song in fight losers. Rocking is thereby suggested to have multiple signaling functions in agonistic and courtship behavior. The song parameters were poorly related with male mating success. Fight winners, rather than fight losers, tended to produce a higher number of calling chirps, which could be explained by the inability of males with high fighting ability to quickly shift from aggression to courtship behavior. The results suggest that increased aggression in fight winners is likely to interfere with subsequent courtship.